PENGARUH MUSIK TERHADAP MOTIVASI BELAJAR dan EMOSIONAL SISWA DALAM PEMBELAJARAN DI SEKOLAH DASAR - Ricky Avandra; Farida Mayar; Desyandri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Music is art in the form of sound produced from various musical instruments or vocals which are arranged harmoniously, rhythmically and melodically. Music can be used in the learning process of elementary school students. Music can increase students' learning motivation by providing an uplifting and interesting atmosphere for students in the learning process. In addition, music can also help improve student focus and concentration in learning. Research shows that music can affect a person's emotions, including students. Music that has a fast tempo can increase student excitement and enthusiasm, while slower music can help calm and relax students. Therefore, music can help reduce student stress and anxiety in learning. Therefore, the authors are interested in conducting a literature study on the effect of music on students' learning and emotional motivation in elementary schools. The purpose of this study is to provide benefits to readers by increasing understanding and knowledge about the use of music in learning can increase students' learning motivation in elementary schools. This research uses the method of literature research (Literature Research). Based on the results of the literature study that has been done, it can be concluded that music can influence students' motivation and emotions so that learning is carried out more fun.